1980
DOI: 10.1002/cjce.5450580410
|View full text |Cite
|
Sign up to set email alerts
|

Intraparticle effects in char combustion steady state analysis

Abstract: A model is developed to study the intraparticle effects of char combustion which incorporates the reactions, C + 1/202 → CO, CO + 1/202 → CO2 and CO2 + C → 2CO with appropriate intrinsic kinetics. Based on some limiting cases a feasibility region, inside which the solution should lie, is developed. In almost all cases the major product is CO with CO2 production 2 to 3 orders of magnitude lower. A maximum of three steady states is observed for the parameters chosen. The combustion rate decreases with increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1
1

Year Published

1981
1981
1994
1994

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
3
1
1
Order By: Relevance
“…In general, it was found that at the ambient conditions used the multiplicity of the problem manifests itself, whenever multiple solutions arise, in a 1-3-1 pattern. The above result is at variance with the results from the shrinking core models (Caram and Amundson, 1977; Mon and Amundson, 1978; Sundaresan and Amundson, 1980) that revealed the existence of up to five steady states for some Figure 5. Behavior of the Tc, TB vs. Tb and Tp vs. Tb loci at higher intraparticle diffusional limitations.…”
Section: Resultscontrasting
confidence: 70%
See 2 more Smart Citations
“…In general, it was found that at the ambient conditions used the multiplicity of the problem manifests itself, whenever multiple solutions arise, in a 1-3-1 pattern. The above result is at variance with the results from the shrinking core models (Caram and Amundson, 1977; Mon and Amundson, 1978; Sundaresan and Amundson, 1980) that revealed the existence of up to five steady states for some Figure 5. Behavior of the Tc, TB vs. Tb and Tp vs. Tb loci at higher intraparticle diffusional limitations.…”
Section: Resultscontrasting
confidence: 70%
“…The rate expressions used in this study and the references in which they are reported appear in Table I. Undoubtedly, the kinetics and mechanisms of the reactions are more complex (Laurendaeu, 1978), but on the one hand, there are few data in the literature regarding intrinsic reactivities of char or coal to gaseous reactants, and on the other hand, we want to make our results comparable with the results of other researchers who used similar reaction rate expressions (e.g., Caram and Amundson, 1977;Mon and Amundson, 1978;Sundaresan and Amundson, 1980;and Srinivas and Amundson, 1980). However, the development of the mathematical model uses arbitrary reaction rate expressions, and hence the same model can be used with any other rate expressions.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Most of the investigators concentrated their attention on the boundary layer diffusion and reaction effects. In order to isolate the boundary layer problem and study it independently, they either considered the carbon particle impervious to diffusion or, as in Caram and Amundson (1977), Mon and Amundson (1978), and Sundaresan and Amundson (1980), lumped, mostly arbitrarily, the internal diffusion and reaction effects on the gross external surface area of the particle. A hierachy of models of varying complexity was used above for the study of the boundary layer problem and extensive computations revealed some previously unsuspected features of the solution, such as the existence of up to five steady states and quenching and lack of ignition for some range of the model parameters.…”
mentioning
confidence: 99%
“…Αυτό έχει επισημανθεί στις εργασίες των Cwiklinski, Βαγενά, Γεωργάκη και Wei[134,135], που μελέτησαν θεωρητικά την επίδραση των ομογενών αντιδράσεων οξείδωσης του CO και του Η^ στην κινητική συμπεριφορά της καύσης και γενικότερα της αεριοποίησης ρωματιδίων άνθρακα.Ο Γαβαλάς[45] πρότεινε ένα μοντέλο, που χρησιμοποιεί γραμμικές εξισώσεις, για την αεριοποίηση του άνθρακα με οξυγόνο. Το μοντέλο προβλέπει μέγιστο στο ρυθμό της αντίδρασης συναρτήσει της μετατροπής, σε συμφωνία με σχετικά πειραματικά αποτελέσματα[136].Επίσης οι Srinivas και Amundson[137] πρότειναν ένα μοντέλο για την επίδραση της εσωτερικής διάχυσης στην καύση του άνθρακα, που Η εγγενής ταχύτητα της αντίδρασης καύσης ποικίλλει ανάλογα με τη σύσταση και την προέλευση του λιγνίτη[3]. Οι εργασίες των Sergeant και Smith[138] και του Arthur[139], ο οποίος πρώτος προσδιόρισε πειραματικά την εξάρτηση της αναλογίας των παραγόμενων CO και C0 2 από τη θερμοκρασία, είναι κλασσικές πειραματικές μελέτες για την εγγενή ταχύτητα της αντίδρασης καύσης διαφόρων γαιανθράκων.…”
unclassified